In the Middle of the Myth: The Problem of Power in Gender Relations and the Alto Douro Region of Northern Portugal - Parkhurst, Shawn (Anthropologica, 2022)
Recent ethnographic scholarship has divided Iberia into a south of male social dominance and a north of female social dominance or social equality. In this article I critique the sweeping character of these distinctions through a review of ethnographies which describe instances of male dominance in northern Portugal. The particular ecological/economic conditions linked to male power in the north lead me to ask if such conditions might define regions, and regional gender relations, at a level between the local settlement and the broad area designated "the north." Analyzing my ethnographic data from northern Portugal's Alto Douro region, I suggest that they do.